Entrepreneurship Training in Traditional Kulinner Processing (Rengginang) As a Creative Industrial Product That Adds Value to the Sales of Farmers’ Harvest in Sagara Jaya Village Bekasi West Java - Yohana, Corry; Rizki Firdausi Rachmadania (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2020)
The purpose of this community service activity is to equip participants to have an understanding and knowledge of the importance of managing how to process harvested rice into rengginang, from how to manufacture, packaging, to marketing it. The training activities are carried out using the classical method with a discussion / question and answer approach and simulation as well as guidance / consultation carried out both through one last meeting session with participants. The implementation of this training was attended by 54 participants. with this training participants will have the knowledge and insight as citizens who are skilled at managing crops to produce rengginang products thereby increasing opportunities for family financial income and providing provisions to improve living standards for the better. Keywords: entrepreneurship training, processing the yields, adding selling points,